Patients Lacking a KIR-Ligand of HLA Group C1 or C2 Have a Better Outcome after Umbilical Cord Blood Transplantation - Martínez-Losada, Carmen; Martín, Carmen; Gonzalez, Rafael; Manzanares, Bárbara; García-Torres, Estefania; Herrera, Concha (Frontiers in Immunology, 2017)
Donor natural killer (NK) cells can destroy residual leukemic cells after allogeneic hematopoietic stem cell transplantation. This effect is based on the interaction of killer-cell immunoglobulin-like receptors (KIR) of donor NK cells with ligands of the major histocompatibility complex (MHC) found on the surface of the target cells. HLA-C1 subtypes provide the ligand for KIR2DL2 and KIR2DL3 and the HLA-C2 subtypes for KIR2DL1. We have studied the probability of relapse (PR) after single unit unrelated cord blood transplantation (UCBT) in relation to the potential graft-versus-leukemia effect mediated by NK cells present in the UCB by analysing KIR-ligand and HLA-C typing of the receptor. Data from 33 consecutive patients given a single unit UCBT were included. We have considered 2 groups of patients based on the absence or the presence of one of the C-ligands for inhibitory KIR and the incompatibility HLA-C1/2 between UCB and patients. Group A (n=21): the patient lacks a C-ligand for inhibitory KIR present in UCB NK cells, i.e. patients homozygous C1/C1 or C2/C2. Group B (n=12): patients heterozygous C1/C2 in which KIR-mediated GVL effect is not expected (presence of both C ligands for inhibitory KIR in the receptor. With a median follow-up post-UCBT of 93 months, patients with absence of a C-ligand for inhibitory KIRs (group A) showed a lower actuarial PR than patients with both C-ligands (group B): 21±10% vs 68±18% at 2 year and 36±13% vs 84±14% at 5 years (p=.025), respectively. In patients with ALL, the 2-years PR was 36±21% for group A and 66±26% for B (p=.038). Furthermore, group A had a lower incidence of grades II-IV acute graft versus host disease (GVHD) (p=.04). In the setting of UCBT, the absence of a C-ligand (C1 or C2) of inhibitory KIR in the patient is associated with lower PR, which is probably due to the graft versus host leukemia effect caused by UCB NK cells that lack a ligand for the inhibitory KIR 2DL1 / 2DL2 / 2DL3.